Commercial oats in gluten-free diet: A persistent risk for celiac patients - Rodríguez, Juan Manuel; Estévez, Virginia; Bascuñán, Karla; Ayala, Jimena; Araya, Magdalena (Frontiers in Nutrition, 2022)
Background. Gluten-free diet is the treatment of celiac disease and other gluten-related disorders and excludes wheat, rye, and barley, while oats inclusion/exclusion has long been a matter of debate. A logo or catchphrase indicating the gluten-free condition in a product is all the consumer relies on to accept the product as suitable for his/her treatment. The oat-based gluten-free products represents a small market, which may have changed and become more limited during covid19 pandemic. Objective. To assess gluten contamination in all labeled oat-based gluten-free local and imported products available in the market, comparing them to matched regular gluten containing counterparts. As a secondary objective, unconventional flours available in the same sale points were also assessed. Results. The search yielded 25 gluten-free labeled oat flours, rolled, and instant cereals, which were compared to 27 regular gluten containing equivalents. Gluten content was above the local (5ppm) and the Codex Alimentarius cutoff (20ppm) in 40% and 36% of the gluten-free labeled products, respectively. When all positive products were analyzed together, there were no differences in gluten content between labeled and unlabeled products. Locally produced products were more expensive, while rolled/instant oats were less contaminated than flours (p= 0.01). Precautionary labels advising presence of gluten as allergen was omitted in 37.0% of regular products. Only 33.3% of unconventional flours obtained from open markets and sold in bulk, were gluten contaminated. Conclusions. Oat-based gluten-free products are currently highly contaminated. It is urgent to regulate them and implement protocols that allow safe consumption of these products.